Toll-like receptor 3 activation decreases porcine arterivirus infection - Sang, Yongming; Ross, Christopher R.; Rowland, Raymond R. R.; Blecha, Frank (My University, 2013)
Porcine reproductive and respiratory syndrome virus (PRRSV) is an RNA virus that initiates infection in pulmonary alveolar macrophages (PAMs), elicits weak immune responses, and establishes a persistent infection. To understand the role of dsRNA intermediates in eliciting host immunity, we sought to determine if toll-like receptor-3 (TLR3), a well-known dsRNA sensor, is involved in the regulation of PRRSV infection. TLR3 gene expression was increased in PAMs of congenitally infected 2-wk-old pigs. Stimulation of PAMs with dsRNA increased gene expression for TLR3 and interferon-β and suppressed PRRSV infectivity. To investigate activation and signaling parameters, expression constructs of wild-type and functional-domain-truncated porcine TLR3 were used in cell transfection studies. When cells that overexpressed porcine TLR3 were stimulated with dsRNA a rapid and robust calcium influx was induced. Moreover, ligand activation of porcine TLR3 expressed in MARC-145 cells elicited an antiviral response to PRRSV. Conversely, transfection of PAMs with small-interfering RNA targeting porcine TLR3 resulted in up to 80% suppression of TLR3 mRNA expression and an increase in PRRSV infectivity. These data provide fundamental genetic and molecular information for porcine TLR3, and implicate its involvement in PRRSV infection, findings that may suggest new strategies to limit this costly pandemic disease.
Keywords: Porcine reproductive and respiratory syndrome virus; Toll-like receptor-3; Pigs